Penciptaan Permainan Digital Edukatif Berbasis Wawasan Budaya Dan Pendidikan Karakter - Samuel Gandang Gunanto (Institut Seni Indonesia Yogyakarta, 2016)
The phenomenon of digital games, or better known by the term game, developed rapidly in the last two decades. This process received a lot of attention from various parties, there is the view of the negative side there is also viewed from the positive side. Lack of game developers on educational game resulted in the least variations of development, it is still around about education and learning about animals, get to know the profession, recognizes objects, learn to count, learn to read or other contents were first developed in the form of interactive multimedia. These forms still have the impression of being a tutor system of learning and less immersive of the gaming world.The research and creation developed an immersive aspect of a game that is tangible for teaching a moral education, specifically about